A Comparative Study of Rural Entrepreneurship Romania – Greece. (2016) - Harpa, Elena; Moca, Sorina; Rus, Dana
Abstract: The present study is based on statistic information regarding the key-indicators of rural development, on different country reports and recent articles regarding the development of rural entrepreneurship in the two countries which are the subjects of the study. The global economic indicators continue to present the effects of the economic crisis, as well as the differences between rural and urban areas and between the member states. The environment parameters confirm this variety between the European countries and regions, but they show general improvement in different domains.